Assessoria virtual para promoção de desenvolvimento socioemocional: avaliação de um programa para professores do ensino fundamental - Santos, Juliana Pinto dos (Universidade Federal de São Carlos, 2023)
The teacher is a fundamental figure in the learning process of social skills in the School context, in articulation with academic learning. This articulation involves teaching strategies that require, in addition to mastering the academic content, a good repertoire of social educational skills from the teacher and their continued training in this direction. For this, guidance and support through specialized advisory is essential. The present study focuses on the final stage (module 4) of a process of continuing education for teachers, whose objective was the construction, implementation and evaluation of virtual advisory for teachers to promote socioemotional development at school. To this end, module 4 included making resources and guidance sheets available in a virtual environment and advising teachers to develop, apply and evaluate a social skills program with their class of students. This thesis is composed of three chapters. Chapter I describes the process of analyzing materials and preparing guidance sheets for Elementary School teachers to promote socio-emotional development in the classroom, as well as evaluating the acceptability and feasibility of using these sheets from the teachers' perspective. Sixty-nine resources were selected and guidance sheets were created to be used by the teachers participating in module 4. Based on the data, the acceptability and positive evaluation of the teachers regarding the application of the resources with the students was noted. In Chapter II, the process and results of the virtual assistance offered to three Elementary School teachers are evaluated. The results, analyzed qualitatively and quantitatively, showed effectiveness, acceptability and viability of the online advisory process in the performance of teachers and promotion of students' socio-emotional development. Finally, Chapter III aimed to evaluate the impact of this program, guided by the advisory process, on: (a) the repertoire of social skills and (b) academic performance of students and (c) on the HSE of the three teacher’s participants. Tools from the virtual environment were used to provide resources and guidance sheets, record teaching plans and application reports, as well as self-assessment by teachers and assessment by the advisory staff. Students' assessment instruments were also applied in relation to the HS repertoire, behavior problems and academic competence. In general, positive changes were identified in the social and academic performance of the students and the social educational skills of the teachers. Furthermore, the participants made positive evaluations of the program. The set of studies suggests the viability of continuing education for teachers in social skills and social educational skills, with specialized support, in the EaD format. Positive aspects of the work, social and scientific contributions, as well as limitations and aspects to be improved are discussed
Virtual advisory to promote socio-emotional development: evaluation of a program for elementary school teachers
Keywords: Desenvolvimento socioemocional; Professores; Habilidades sociais educativas; Ensino à distância; Assessoria; Socio-emotional development; Teachers; Educational social skills; Distance learning; Advisory; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::APRENDIZAGEM E DESEMPENHO ACADEMICOS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::ENSINO E APRENDIZAGEM NA SALA DE AULA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO